Role of right posterior parietal cortex in maintaining attention to spatial locations over time - Malhotra, P; Coulthard, E; Husain, M (2009)
Recent models of human posterior parietal cortex (PPC) have variously emphasized its role in spatial perception, visuomotor control or directing attention. However, neuroimaging and lesion studies also suggest that the right PPC might play a special role in maintaining an alert state. Previously, assessments of right-hemisphere patients with hemispatial neglect have revealed significant overall deficits on vigilance tasks, but to date there has been no demonstration of a deterioration of performance over timea vigilance decrementconsidered by some to be a key index of a deficit in maintaining attention. Moreover, sustained attention deficits in neglect have not specifically been related to PPC lesions, and it remains unclear whether they interact with spatial impairments in this syndrome. Here we examined the ability of right-hemisphere patients with neglect to maintain attention, comparing them to stroke controls and healthy individuals. We found evidence of an overall deficit in sustaining attention associated with PPC lesions, even for a simple detection task with stimuli presented centrally. In a second experiment, we demonstrated a vigilance decrement in neglect patients specifically only when they were required to maintain attention to spatial locations, but not verbal material. Lesioned voxels in the right PPC spanning a region between the intraparietal sulcus and inferior parietal lobe were significantly associated with this deficit. Finally, we compared performance on a task that required attention to be maintained either to visual patterns or spatial locations, matched for task difficulty. Again, we found a vigilance decrement but only when attention had to be maintained on spatial information. We conclude that sustaining attention to spatial locations is a critical function of the human right PPC which needs to be incorporated into models of normal parietal function as well as those of the clinical syndrome of hemispatial neglect.